The Conception of the Devil in the “Shrill Sound Of The Ultimate Trumpet” (1670) by Father Klemens Bolesławiusz (1625–1689), in Comparison with John Milton’s (1608–1674) “Paradise Lost”, Christopher Marlowe’s “Doctor Faustus” (1564–1593), and Joost Van De - Wicher, Andrzej (Diabeł Boruta w dawnej kulturze polskiej, 2021)
It is not the aim of the present article to show that Bolesławiusz’s poem, published in Poznań in 1670, deserves to be viewed on a par with such masterpieces as John Milton’s Paradise Lost (1667), Christopher Marlowe’s Doctor Faustus (1604), or Joost van den Vondel’s Lucifer (1654), which represent the very best in the English and Dutch literatures of the 17th century. It has to be remembered that Dutch literature, even if it later came to be regarded as rather marginal, in the 17th century was undergoing its golden age. Nevertheless, it seems that some of Bolesławiusz’s ideas and visions, concerning especially the devils, are comparable with Milton’s, Marlowe’s and Vondel’s satanological conceptions. Such comparisons are hazardous enough, bearing in mind that we are talking about various literary genres, Bolesławiusz’s work being a devotional poem, rather than an epic poem, or a drama. Another thing is that the figures of the Devil or Satan in Milton and Vondel stand in the foreground, while Bolesławiusz’s devils are background characters. Neither is the question of the influence of one writer on another is discussed here, even though Milton could have been influenced by Vondel, and could have known also Marlowe’s play.